Failure analysis of tapered roller bearing inner rings used in heavy truck. (April 2020) - Xu, Xiao-lei; Yu, Zhi-wei
Highlights: Hoop brittle fracture occurred on the tapered roller bearing inner rings. Crack origin were located on laser marking area of small head end of inner ring. Deep and narrow near-surface micro-grooves were introduced by laser marking. Grinding burn leading to thermal softening occurred on the small head end. Abstract: Hoop brittle fracture took place on several tapered roller bearing inner rings during assembling with the intermediate shaft. All the cracking took place on the laser marking area on the small head end of inner ring representative of product identification. Detailed metallurgical analysis revealed that two kinds of metallurgical defects mainly occurred on the small head end of cracked inner rings: (1) several of deep and narrow near-surface micro-grooves resulting from laser marking were distributed dispersively on the small head end of inner ring, (2) the thermal softening resulting from grinding burn occurred on the small head end of inner ring, causing decrease in surface hardness as well as development of tensile stress. The crack origins were all located on the overlapping zone of the laser marking area and grinding burn area. Cracks initiated from the micro-grooves and propagated toward the inner along the axial under the action of assembly stress. The presence of the near-surface micro-grooves as sharp notches on the laser-marked small head end was mainly responsible for the fracture failure of inner rings. The occurrence of the thermal softening layer due to grinding burn on the small end of inner ring, consequently leading to decreasing in the surface hardness and resultant low tensile strength, promoted the crack initiation and propagation.